2021
DOI: 10.1002/adhm.202100894
|View full text |Cite
|
Sign up to set email alerts
|

XPS and ToF‐SIMS Characterization of New Biodegradable Poly(Peptide‐Urethane‐Urea) Block Copolymers

Abstract: New, linear, segmented poly(peptide‐urethane‐urea) (PPUU) block copolymers are synthesized and their surface compositions are characterized with angle dependent X‐ray photoelectron spectroscopy (ADXPS) and time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS). These new PPUU block copolymers contain three types of segments. The soft segment (SS) is poly(caprolactone diol) (PCL). The hard segment is lysine diisocyanate with a hydrazine chain extender. The oligopeptide segment (OPS) contains three types of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Additional characterization such as X-ray photoelectron spectroscopy (XPS) or Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) may be used in the future to provide complementary vertical phase separation information. 33,34…”
Section: Highlighting a Target Materials In A Complex Ternary Blend O...mentioning
confidence: 99%
“…Additional characterization such as X-ray photoelectron spectroscopy (XPS) or Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) may be used in the future to provide complementary vertical phase separation information. 33,34…”
Section: Highlighting a Target Materials In A Complex Ternary Blend O...mentioning
confidence: 99%
“…[18][19][20][21] Recent studies have demonstrated incorporation of bioactive peptide into nylons, 22 however, the use of enzyme-sensitive peptides to control resorption of high molecular weight thermoplastics remains unreported. Zorn and colleagues polymerized oligopeptide segments into polyurethanes 23 for the purpose of improving polymer biodegradation. Their work fully characterized the surface of these peptideincorporated block copolymers, demonstrating that the surface is enriched with the most hydrophobic of the monomer units.…”
Section: Introductionmentioning
confidence: 99%